Neutrinoless double beta decay with and without Majoron-like boson emission in a 3-3-1 model - Montero, J. C. [UNESP]; Pires, C. A.D.S.; Pleitez, V. [UNESP] (My University, 2001)
We consider the contributions to the neutrinoless double beta decays in a SU(3)L⊗U(1)N electroweak model. We show that for a range of parameters in the model there are diagrams involving vector-vector-scalar and trilinear scalar couplings which can be potentially as contributing as the light massive Majorana neutrino exchange one. We use these contributions to obtain constraints upon some mass scales of the model, such as the masses of the new charged vector and scalar bosons. We also consider briefly the decay in which, in addition to the two electrons, a Majoron-like boson is emitted. ©2001 The American Physical Society.